Cold processed oil-in-water emulsions for dermatological purpose: formulation design and structure analysis. (1st June 2014) - Raposo, Sara; Salgado, Ana; Eccleston, Gillian; Urbano, Manuela; Ribeiro, Helena M.
Abstract: The aim of this work is to develop, optimize and characterize cold process emulsions that are stable at acidic pH. The main surfactant was selected according to the hydrophilic lipophilic balance (HLB) concept and surface tension, whereas polymers were selected by viscoelastic measurements and analytical centrifugation. It was showed that the inclusion of methyl vinyl ether/maleic anhydride copolymer crosslinked with decadiene (PVM/MA) increased the storage modulus ( G′ ) of the gels (23.9–42.1 Pa) two-fold and the droplet migration decreased from 3.66% to 0.95%/h. Cetrimide was selected as a preservative based on its microbiological results and additional contribution to the stability of the emulsions. Four emulsions were developed that differed by the co-emulsifier used (PEG-20 glyceril laurate and polyglyceryl-4-isostearate) and the glycol (2-methyl-2, 4-pentanediol and ethoxydiglycol). Viscoelastic measurements and droplet size/microscopic analysis showed that the structure of PEG-20 glyceril laurate emulsion (η' = 76.0 Pa.s at 0.01 Hz and 32.9 ± 3.7 µm, respectively) was stronger compared to polyglyceryl-4-isostearate (η' = 37.4 Pa.s at 0.01 Hz and 37.8 ± 15.7 µm, respectively). Differential scanning calorimetry (DSC) results were in accordance with the latter and showed that PEG-20 glyceril laurate with 2-methyl-2, 4-pentanediol corresponded to the strongest structure (|224.4| W °C g −1 ). This cold process allowed a total production savings of more than 17% when compared to the traditional hot process.